Dynamic adaptive trust evaluation model based on interaction-aware - Feng LI; Li-min SHEN; Ya-li SI; Jing-chun NIU (Tongxin xuebao)
A dynamic adaptive trust evaluation model was established based on interaction-aware.The historical interaction window and trustworthy recommendation number was introduced in overall trust evaluation method,which overcomes the shortage of traditional models that lack the capacity to interaction-aware.The direct trust accumulation method based on interaction satisfaction degree iterative calculation was proposed,which achieved the incentive and penalty iterative strategy based on entity stability factor,and effectively inhibits malicious entities with camouflage.A synthetical recommendation trust aggregating method based on combination of direct and indirect recommendation trust was given,which solved the accuracy low and unreliable problems of traditional recommendation methods by introducing entity familiarity factor and scoring similarity factor.Simulation results show that,compared to the existing trust model,the model can effectively improve the accuracy of trust evaluation,and can provide a better capacity of resisting collusive entities.